Efek Pemberian Ekstrak Kulit Buah Mangga Arum Manis (Mangifera Indica) Terhadap Gambaran Histopatologi Tikus Wistar Jantan Obesitas Yang Diinduksi High Lipid Diet Dan Aloksan - Khoven, Kimi; Theresia, Yohani; Anggraini , Tri Lidya (Syntax Corporation, 2025)
Obesity is a global problem that can cause pancreatic damage through increased oxidative stress. Mango peel contains bioactive compounds such as flavonoids, tannins, steroids, terpenoids, alkaloids, saponins, and polyphenols that have antioxidant functions. This study aims to evaluate the effect of giving mango arum manis fruit peel extract on the histopathology of pancreatic tissue and blood sugar levels of obese male Wistar rats induced by high lipid diet and alloxan. This study used a post-test only control group design which was divided into a positive group given pioglitazone 3 mg/kg BW, a group given 30 mg/kg BW extract, 60 mg/kg BW extract, and 120 mg/kg BW sweet mango arum fruit peel extract. The results of histopathological examination of pancreatic tissue showed that in all groups there was pancreatic damage with a score of 3, so it did not show significant differences. However, in the examination of blood sugar levels, there were significant differences before and after the administration of sweet mango arum fruit peel extract, which showed the most significant results were the administration of sweet mango arum fruit peel extract at a dose of 30 mg / kg BW and 120 mg / kg BW.